Novel human-derived extracellular matrix induces in vitro and in vivo vascularization and inhibits fibrosis. (May 2015) - Moore, Marc C.; Pandolfi, Vittoria; McFetridge, Peter S.
Abstract: The inability to vascularize engineered organs and revascularize areas of infarction has been a major roadblock to delivering successful regenerative medicine therapies to the clinic. These investigations detail an isolated human extracellular matrix derived from the placenta ( h PM) that induces vasculogenesis in vitro and angiogenesis in vivo within bioengineered tissues, with significant immune reductive properties. Compositional analysis showed ECM components (fibrinogen, laminin), angiogenic cytokines (angiogenin, FGF), and immune-related cytokines (annexins, DEFA1) in near physiological ratios. Gene expression profiles of endothelial cells seeded onto the matrix displayed upregulation of angiogenic genes (TGFB1, VEGFA), remodeling genes (MMP9, LAMA5) and vascular development genes (HAND2, LECT1). Angiogenic networks displayed a time dependent stability in comparison to current in vitro approaches that degrade rapidly. In vivo, matrix-dosed bioscaffolds showed enhanced angiogenesis and significantly reduced fibrosis in comparison to current angiogenic biomaterials. Implementation of this human placenta derived extracellular matrix provides an alternative to Matrigel and, due to its human derivation, its development may have significant clinical applications leading to advances in therapeutic angiogenesis techniques and tissue engineering.